The Influence of Product Quality, Service Quality, and Customer Trust on Customer Satisfaction in the Shopee Application - Lusi Winda Silaban; Yana Diana; Megasari Gusandra Saragih (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to determine whether product quality partially has a positive and significant effect on customer satisfaction in the Shopee application. Does service quality partially have a positive and significant effect on customer satisfaction in the Shopee application? Does customer trust partially have a positive and significant effect on customer satisfaction in the Shopee application? Do product quality, service quality, and customer trust simultaneously have a positive and significant effect on customer satisfaction in the Shopee application? The research method is quantitative associative research with the help of the SPSS program. This study uses multiple linear regression. The sample in this study was 96 respondents. The results show that product quality partially has a positive and significant effect on customer satisfaction in the Shopee application. Service quality partially has a positive and significant effect on customer satisfaction in the Shopee application. Customer trust partially has a positive and significant effect on customer satisfaction in the Shopee application. Product quality, service quality, and customer trust simultaneously have a positive and significant effect on customer satisfaction in the Shopee application.